Functional and ecological correlates of the primate jaw abductors. Issue 5 (24th September 2021) - Dickinson, Edwin; Pastor, Francisco; Santana, Sharlene E.; Hartstone‐Rose, Adam
Abstract: While the adductor musculature of the primate jaw has been extensively analyzed within the context of dietary and social ecology, little is known about the corresponding muscles of jaw abduction . Nonetheless, these muscles significantly contribute to a species' maximum gape potential, and thus might constrain dietary niche diversity and impact social display behaviors. In this study, we quantify the architectural properties of the digastric (a jaw abductor) and lateral pterygoid (a jaw abductor and anterior translator) across a broad sample of male and female anthropoid primates. We test the hypothesis that the abductor musculature reflects specialization to dietary and behavioral ecology. Our sample comprises 14 catarrhine and 13 platyrrhine species spanning a wide range of dietary and social categories. All specimens were sharp dissected and muscles subsequently chemically digested using a standardized protocol. Our findings demonstrate that relative fascicle lengths within the lateral pterygoid (but not the digastric) are significantly greater within species that habitually consume larger food items. Meanwhile, canine length is more strongly associated with fascicle lengths in the digastric than in the lateral pterygoid, particularly within males. Neither dietary mechanical resistance nor the intensity of social competition relates to the size or architectural properties of the jaw abductors. These findings suggest that dietary—and to a lesser extent, socioecological—aspects of a primate's life history may be reflected in the architecture of these muscles, albeit to varying degrees. This underlines the importance of considering the complete masticatory apparatus when interpreting the evolution of the primate jaw.